Fatal systemic angiomatosis with widespread sclerotic skeletal changes, diagnosed with the aid of a bone marrow biopsy: the lymphatics enter the bone marrow - Rudzki, Zbigniew; Lovell, Richard; Miller, Ben; Murthy, Vidhya; Paneesha, Shankara; Pratt, Guy; Smith, Neil (Polish Journal of Pathology, 2018)
A 56-year-old female presented with popliteal venous thrombosis, splenomegaly, and sclerotic bone lesions. Bone marrow biopsy showed fibrosis, proliferation of abnormal blood vessels and lymphatics, bone remodelling, and no significant changes in haematopoietic elements. Following a relatively indolent initial clinical course, one year later she rapidly deteriorated and died of respiratory failure associated with widespread disease. Ingrowth of podoplanin+ lymphatics mixed with CD34+/podoplanin– blood vessels into the bone marrow is a new finding and may be a unique feature of this disease.